A Profile of the Oil and Gas Industry - Herkenhoff, Linda (Business Expert Press, 2014)
Ebook from IG Library ; We drilled in the right place-we were simply 30 million years too late .Richard Bray President of Sohio on drilling the Mukluk Prospect ,Beaufort Sea ,1983 .As early as 3000 BC ,we know that the people of Mesopotamia were using crude oil as a tar for building ships and houses so ,it is not by any means a new industry ,but it is a volatile one .Oil and gas are important to every aspect of our economy yet this industry is distinguished by its combination of increasing demands and decreasing discovery volumes ;and it is an industry shrouded in an environment of extremely volatile pricing .Although the profits enjoyed by the oil and gas industry are enormous ,the industry remains one of the most capital intensive in a world where rising ...